Penyuluhan Penggunaan Dan Keamanan Obat Tradisional Di Desa Benteng Gajah Kecamatan Tompobulu Kabupaten Maros - LASABUDA, TAUFAN EKA PUTRA (PABBURA : Health Service Journal, 2024)
Education about the use of traditional medicines is an important effort to increase public understanding and awareness of the potential benefits and risks associated with the use of medicines based on these natural ingredients. To support this, education is carried out regarding the use and safety of traditional medicines. Extension also teaches people about the right dosage, the right processing method, and choosing safe and quality products. This aims to reduce the risk of inappropriate use of traditional medicines so that people can use them wisely and effectively as part of their health care. Participants in this activity are the people of Benteng Gajah Village, Maros Regency. The presentation of the material is delivered via audio-visual devices, followed by discussion and questions and answers regarding the material or other related matters. Pretest and posttest were conducted to assess initial knowledge and after education. The pretest results showed the level of public understanding regarding the use and safety of traditional medicine was 45%. The posttest results after education showed an increase in public understanding of 99.30%. The implementation of this outreach activity has increased public knowledge regarding the use and safety of traditional medicine.